The Influence of the Technology Acceptance Model (TAM) on the Intention to Use E-Commerce Accounting Information Systems in the TikTok Shop Application (A Case Study of STIE GICI Pondok Gede Students - Musfitria, Anessa; Iswandi, Mei; Sari, Clara Dian Puspito (Madani: Jurnal Ilmiah Multidisiplin, 2025)
He use of technology has developed significantly in the era of globalization. With the rapid advancement of information technology, the dissemination of information in the business world through internet networks has increased considerably. This development provides convenience for both consumers and producers to establish cooperative relationships in online sales, commonly known as e-commerce. One of the relatively popular e-commerce platforms today is TikTok. This research is based on the Technology Acceptance Model (TAM) theory. This study uses a quantitative approach with an associative research type. The research object is STIE GICI Pondok Gede Campus. Data collection was carried out using a questionnaire distribution technique. The sample was selected using a purposive sampling method, resulting in 57 respondents. The respondents of this study were active students from the 2021/2025 academic cohort. The data analysis used is multiple linear regression with SPSS version 30. The results of this study concluded that: 1) partially, the variables of ease of use, perceived usefulness, risk, and attitude toward use do not have a positive influence, while the trust variable has a positive influence; 2) simultaneously, all variables have a positive influence.